2017
DOI: 10.4314/sajas.v47i1.13
|View full text |Cite
|
Sign up to set email alerts
|

<i>In situ </i>ruminal degradability of protein feeds with distinct physical forms: a meta-analysis

Abstract: In ruminant livestock, rumen undegradable protein (RUP) derived from the diet and microbial protein synthesized in the rumen are essential for animal survival, maintenance, growth, production, and reproduction. RUP is influenced by diet composition, physical form, and ruminal metabolism. Here, we aimed to evaluate the ruminal degradability of protein feeds with different physical forms (meal versus grain) through a meta-analysis study. A database, composed of 45 treatments from 12 studies carried out in Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is more appropriate to assume all negative lag-times for degradation to commence at 0 h, especially feeds classified as concentrates. Studies that seek to predict or simulate degradation rates should separate datasets based on which of the two models were used to estimate degradation rates to avoid under predicting the rate of degradation, in a similar way to the meta-analysis of Busanello et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more appropriate to assume all negative lag-times for degradation to commence at 0 h, especially feeds classified as concentrates. Studies that seek to predict or simulate degradation rates should separate datasets based on which of the two models were used to estimate degradation rates to avoid under predicting the rate of degradation, in a similar way to the meta-analysis of Busanello et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This trend is consistent with the positive significant correlation between incubation time and PD observed in this study. A meta-analysis finding by Busanello et al [ 27 ] showed that the degradation of dry matter was similar for meals (oil cakes) and grains (concentrates).…”
Section: Discussionmentioning
confidence: 99%